1984
DOI: 10.1128/aac.26.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inoculum size on comparative susceptibilities of penicillinase-positive and -negative Neisseria gonorrhoeae to 31 antimicrobial agents

Abstract: The effects of two inoculum sizes (104 and 106 CFU) on the MICs of 20 beta-lactam antibiotics, 4 aminoglycosides, and 7 other antimicrobial agents were compared for 102 unselected strains of Neisseria gonorrhoeae (26 penicillinase positive and 76 penicillinase negative), with three replicates for each test. The method was agar plate dilution on Muelier-Hinton agar supplemented with 1% hemoglobin and 1% IsoVitaleX. For penicillinase-positive strains, a large inoculum (106 CFU) increased the MIC 216-fold for ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The comparability of Etest and agar dilution observed in this study, has also been observed elsewhere, particularly for cephalosporins [ 21 23 ]. MIC differences in our study could be due to agar media and inoculum size differences as established previously [ 24 , 25 ], along with varying levels of comparability between different disk diffusion methods and agar dilution and/or Etests [ 26 30 ]. Identified agar media differences in this study (data not shown) in general agree with data presented from other studies, including that cephalosporin MICs were generally slightly higher from agar dilution with GC agar compared with Etests [ 21 23 ], MICs from Etests with chocolate agar were higher [ 31 ], as well as differing MIC variation depending upon which media was used for agar dilution [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 89%
“…The comparability of Etest and agar dilution observed in this study, has also been observed elsewhere, particularly for cephalosporins [ 21 23 ]. MIC differences in our study could be due to agar media and inoculum size differences as established previously [ 24 , 25 ], along with varying levels of comparability between different disk diffusion methods and agar dilution and/or Etests [ 26 30 ]. Identified agar media differences in this study (data not shown) in general agree with data presented from other studies, including that cephalosporin MICs were generally slightly higher from agar dilution with GC agar compared with Etests [ 21 23 ], MICs from Etests with chocolate agar were higher [ 31 ], as well as differing MIC variation depending upon which media was used for agar dilution [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 89%
“…It is well known from in-vitro studies that a high density of /Mactamase producing bacteria diminishes the effect of /Mactam antibiotics (inoculum effect). The concentration of bacterial /Mactamases probably correlates with the density of the bacterial inoculum (Sabath et al, 1975;Eng, Smith & Cherubin, 1984;Hall & Opfer, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Hall and Opfer have also found that inoculum size had little influence on MICs for penicillinase-negative N. gonorrhoeae (2). The National Committee for Clinical Laboratory Standards (7) recommends that an inoculum of 104 be delivered to the antibiotic-containing plates in agar dilution tests.…”
Section: Discussionmentioning
confidence: 98%